Alteration of Physico-mechanical Properties of Black Tilapia Scale Gelatins using UVA and UVC Irradiation - Sockalingam, Kanageswary; Abdullah, Hasan Zuhudi; Idris, Maizlinda Izwana (International Journal of Integrated Engineering, 2022)
Fish gelatin is abundant, relatively low cost and biodegradable. However, their inferior mechanical and rheological properties make them less competitive compared to mammalian gelatins. Hence, the effects of Ultraviolet (UV) irradiation on the properties of scale gelatins were analyzed. Gelatins were extracted from black tilapia scale via thermal extraction method. The gelatins were then subjected to Ultraviolet-A (UVA) and Ultraviolet-C (UVC) irradiation for 0.5 to 2.5 h and the changes in gel strength, viscosity, and melting temperature were observed. Results obtained show a marked increase in the gel strength and viscosity of the gelatins. However, the effects on the melting temperature are minimal. Treatment with UVA and UVC improved the gel strength of the gelatins up to 5.12 Â± 0.22 N and 4.75 Â± 0.09 N, respectively. Further analysis using Fourier Transform Infrared (FTIR) Spectroscopy showed crosslinking formation in the polypeptide chains induced by UV irradiation. UVA was found to be more effective in enhancing the properties of scale gelatins compared to UVC. In general, UV-irradiated scale gelatins showed excellent properties compared to the commercial bovine gelatin. Results indicated the prospects of employing UV treatment in enhancing the properties of fish gelatin.